Challenges to overcome in a randomised trial for Proper Understanding of Recurrent Stress Urinary Incontinence Treatment in women: the PURSUIT RCT - Caroline Pope; Madeleine Cochrane; Clare Clement; Yumeng Liu; Sangeetha Paramasivan; Sian Noble; Stephanie J MacNeill; Amanda L Lewis; Jodi Taylor; Bethanie Fitzgerald; Nikki Cotterill; Tamsin Greenwell; et al. (Health Technology Assessment)
Background Recurrence or persistence of symptoms after interventions to treat stress urinary incontinence in women is common, but without robust evidence to base treatment recommendations. Objectives To investigate whether endoscopic or surgical treatments for stress urinary incontinence in women are effective and cost-effective. Design A multicentre, unblinded, parallel-group randomised controlled trial. Setting Fifteen centres across the United Kingdom. Participants Adult women with recurrent or persistent stress urinary incontinence. Intervention Individual randomisation to endoscopic (urethral bulking) or surgical (autologous sling, colposuspension, artificial urinary sphincter) interventions. Women randomised to surgery chose their operative intervention. Main outcomes Primary outcome self-reported International Consultation on Incontinence Questionnaire-Urinary Incontinence-Short Form at 1 year post randomisation. Secondary outcomes included International Consultation on Incontinence Questionnaire-Urinary Incontinence-Short Form, Patient Global Impression of Improvement and Pelvic Organ Prolapse/Urinary Incontinence Sexual questionnaires up to 3 years post randomisation, operative assessment measures and adverse events, cost-effectiveness from National Health Service and societal perspectives (quality-adjusted life-years and International Consultation on Incontinence Questionnaire-Urinary Incontinence-Short Form) at 1 year, and a secondary care perspective (quality-adjusted life-years) at 3 years. Semistructured qualitative interviews at baseline (post randomisation), follow-up (3–6 months) and longer-term (12 and 36 months), to explore stress urinary incontinence generally, the acceptability and attitudes to treatments and to improve understanding of outcomes. Qualitative interviews with clinicians at baseline were focused on potential difficulties of recruitment and optimising patient-facing information and training materials for clinicians. Results Fifty-five women were deemed eligible after screening (n = 328 screened) from October 2019 to June 2022. Twenty-four eligible women consented, and 23 were randomised (between January 2020 and July 2022) from 8 sites with the average age of 57 years (standard deviation: 10.7) and all self-reported ‘white’ ethnicity. Participants reported a median International Consultation on Incontinence Questionnaire-Urinary Incontinence-Short Form score at baseline of 16 (interquartile range: 13–19) and mean post-void residual volume of 4.64 ml (standard deviation: 8.45). Eleven participants received their allocated intervention, 2 participants withdrew prior to receiving their intervention and 10 were waiting for their intervention when the study closed. The most common reason for declining participation was a treatment preference (n = 14). Recruitment training sessions and recruitment tips documents were developed and implemented to address challenges centred around patient treatment preferences and clinicians’ equipoise. However, the most important recruitment challenge was the low number of eligible patients, driven primarily by the COVID-19 pandemic preventing referrals and surgery, and related wider issues in the National Health Service which led to study closure in January 2023. Conclusion In its early stages, the initial recruitment rate was on target (four participants randomised in the first 3 months of recruitment), but once the pandemic started, the study was unable to recruit and so closed early. The main limitation was the occurrence of the global pandemic soon after the commencement of recruitment, profoundly affecting service delivery and patient presentations. Under normal healthcare service conditions, the study may be deliverable. Limitations Failure to recruit under pandemic conditions rendered the study unfeasible. Future research Practical experience with the study and development of patient-facing and staff training materials will help delivery of the study once patient referrals and healthcare services fully return to normal. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 17/95/03. Plain language summary Urinary leakage with physical activity, or stress urinary incontinence, affects about a quarter of women after pregnancy and at other times. Treatment options include surgery or a bulking injection into the bladder, but symptoms can continue after treatment, known as recurrent, or persistent, stress urinary incontinence. It is not known which treatment is best for women who have already had a treatment. This study aimed to establish whether an operation or endoscopic bulking injections are better for treating recurrent or persistent stress urinary incontinence. The study aim was for 250 women across the United Kingdom with recurrent stress urinary incontinence to take part, and recruitment started in January 2020. Fifty-five women from 15 hospitals were identified as suitable, and 23 women consented to take part and were randomly allocated (by chance) to a treatment group (surgery or bulking injection). Women in the surgery group decided which operation to have in consultation with their doctor. Women were asked to complete questionnaires at the start of the study, and again later, covering general health, urinary symptoms and the effect of those symptoms on everyday life. Some women were interviewed to explore their attitudes to the treatments and understand how they manage after having treatment. The most common reason women gave for not wanting to take part was that they had a treatment preference. Eleven women received their allocated treatment. However, the COVID pandemic and wider issues within the National Health Service made it impossible to identify enough suitable women, and treatments were prevented for a long period, so the study closed early in January 2023. Unfortunately, it is not possible to make conclusions from the results collected due to the low number of women in the study.